(untitled) (Al-Academy, 2016)
Comes interest in the subject matter in the selection of the Family industry globally as one of the important industries which have developed a clear and significant in recent years, to look at these products and designs to their functional importance have appeared in recent years, the phenomenon of the small spaces because of housing Population density showed the need to find a spare Furniture fit these small spaces On this basis, determine the objective of this research is to arrive at a design techniques for dual-family employee for small spaces research sample included a double family manufactured in laboratories industry Furniture in Baghdad and local research sample includes family double Decker.Research focused on the first four chapters of eating them research problem and its importance, its goals and limits as well as identifying some of the terms of the subject matter. The theoretical framework addressed in Chapter II Detectives several represented axes essential for the design of double beds, such as the definition of the types and forms of family double-decker as well as the functions and reasons for use through the basics of appropriate measurements and angles of the product to keep the human body and to provide adequate comfort during use and thus the efficiency of the work product, also included a chapter Detectives several eating Study of furnishing and double beds, and all embodied in the concept of furniture types and forms of family dual mechanism of human body measurements The second section guarantees the system small spaces and design directions. This section included a study of the conditions of the various sit and lie down and sufficient space for him, as well as the study of the possibilities of movement in building the backbone of the man and its relationship to design the dual family. Third and Me Study of the role of technology in the design of systems change the double-decker family. , And this section contains a study on the appropriate functional double-decker Ajzaalasrh through a blueprint for the human body measurements and its specificity. The researcher in procedures design analysis derived form of axes through indicators that emerged from the theoretical study as well as field visits to the researcher to civil laboratories for dual family industry and small spaces.